A Fault Diagnosis Scheme for Aircraft Multibranches Wiring Network Based on Matching Algorithm. (18th June 2015) - Liwen, Wang; Lu, Zhang; Meng, Xu; Xudong, Shi
Abstract : This paper mainly describes a fault diagnosis scheme for aircraft multibranches wiring networks. The background theory is based on the matching algorithm with theoretical reflection waveform and realistic reflection waveform. Firstly, a numerical model with a comprehensive database was built to create the theoretical waveform of the measured wiring network. On the other hand, the realistic reflection waveform of the measured wiring network can be collected by reflectometry detection system. Then, the waveform matching algorithm and fault diagnosis algorithm were applied to detect the fault type and fault location in the measured wiring network. With all the steps above, the fault diagnosis scheme was designed and realized. Finally, a multibranches wiring network, which includes two branches, and one of its branches contains two subbranches with different types of faults, was built to verify the fault diagnosis scheme and the results show that the scheme is an effective way to diagnose faults in multibranches wiring network.